Harnessing Crataegus rosei “tejocote” for biogenic synthesis of copper nanoparticles and cytotoxicity in normal and cancer cells - Gilmer David Cab-Torres; Lluvia López; Daniela Salado-Leza; Gabriela Navarro-Tovar (Nano Trends)
The biogenic synthesis of metallic nanoparticles (MNPs) using plant extracts has been proposed as a facile and low-cost process that can enhance the antimicrobial and anticancer properties of those MNPs, suggesting that the plant extract capping can also improve biosafety. In this work, copper nanoparticles (CuNPs) (86 ± 46 nm) were synthesized using a Crataegus rosei “tejocote” extract (rich in polyphenols and flavonoids), and the obtained particles were evaluated in human keratinocytes HaCaT cells (healthy cells) and tumor prostate PC-3 cells to determine toxicity and antitumor activity, respectively. The plant extract showed non or slight cytotoxic effects in both HaCaT and PC-3 cells at the tested concentrations. On the other hand, CuNPs synthesized with C. rosei extract showed an IC50 =120 ± 1.13 µg/mL in HaCaT cells, but in tumor PC-3 cells the IC50 = 491 ± 1.06 µg/mL. It is showed that C. rosei capping is insufficient to tune the oxidative stress in healthy cells exposed to CuNPs at higher concentrations, and, that higher concentrations of CuNPs are required to reduce the cell viability in <70 % in tumor PC-3 cells. Thus, a further study with different biogenic synthesized CuNPs particle size could determine different effects on the same models. It is also relevant to carry out in vitro analysis with other cancer cells and biomarkers.